Ad Women: How They Impact What We Need, Want, and Buy - Sivulka, Juliann (Prometheus, 2008)
Most of the workers in advertising, the media, retail, and fashion are women. Holding key marketing and advertising positions, women shape the basic promotional appeal of almost every consumer product in America.How did the advertising business go from a handful of women in a man's world to women working in virtually every mass consumer goods industry in America in the space of the twentieth century? Ad Women tells the story of how women have risen to the top of the advertising profession. Anyone who has followed the rise of Mad Men's Peggy Olson from secretary to copywriter will be interested in the story of her real-life counterparts.Juliann Sivulka, a former marketing communications manager and now an advertising educator, describes how, at the beginning of the twentieth century, the recognition of women as primary consumers resulted in the hiring of more women to promote products aimed at the women's market. At that time manufacturers began to emphasize color, fashion, and style, while advertising embraced a new language of persuasion aimed at women consumers. Soon agencies were recruiting an ensemble of businesswomen―copywriters, product designers, merchandisers, fashion and beauty experts, home economists, editors, and publicists. Through close collaboration with manufacturers, mass media, and retailers, they participated in developing strategies to convince women to buy goods and wove their selling messages into women's reading, shopping, housework, and leisure activities.Sivulka follows three key periods in the history of American advertising, which represent eras of major social change for women (1880-1920, the 1920s, and the 1970s). She discusses the effect on advertising of such controversial issues as the women's movement, minorities, and consumer activism, and devotes an entire chapter to the contributions to advertising of African American, Hispanic, and Asian American women in the twentieth century.Copiously illustrated with portraits of early ad women and examples of their work, this thoroughly researched and engagingly written survey of women in advertising will fascinate marketing students, women's studies scholars, and everyday consumers.
Keywords: Business History and gender